Herding dan Overconfidence dalam Investasi Gen Z: Dampak dan Moderasi Literasi Keuangan - Felycia Sugianto, Devina; Inggrit Wijaya, Liliana; Silvia Sutejo, Bertha (DINASTI RESEARCH, 2024)
This research aims to examine the influence of behavioral biases among Generation Z investors in Indonesia specifically herding and overconfidence on investment decision making, with financial literacy as a moderating variable. This study employs a quantitative approach using SEM (Structural Equation Modeling) analysis. Data was collected by distributing questionnaires to Generation Z investors in Indonesia aged 17 to 27 who have invested in the Indonesia Stock Exchange (IDX). The results indicate that the herding and overconfidence behavioral biases significantly impact investment decisions. Finally, the moderating variable of financial literacy strengthens the relationship between the herding and overconfidence biases and investment decisions.